Peningkatan Kadar Hemoglobin melalui Pemeriksaan dan Pemberian Tablet Fe Terhadap Remaja yang Mengalami Anemia Melalui “Gerakan Jumat Pintar” - Rini Nuraeni; Puspa Sari; Neneng Martini; Sri Astuti; Lina Rahmiati (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
Anemia iron deficiency in adolescent girls have an impact to decrease of productivity work and academic ability in school and long term can lead to complications in pregnancy and childbirth. Therefore, it is necessary prevention and control of anemia with the provision of iron. The purpose of this research was to determine the intake of iron supplementation and the effectiveness of giving oral iron supplementation to increase levels of adolescent girl’s hemoglobin. This is interventional research with one group pretest-posttest design. The Sample in this research is adolescent girls, with a total sample of 31 respondents. The respondent received iron supplementation every Friday, for one month through “Gerakan Jumat Pintar”. The nutritional intake data were obtained from the food record for 3 days. Statistically, the analysis used is Wilcoxon. The result indicated that anemia iron deficiency in adolescent girls is decrease from 42% to 22.6%. Adolescent girls who suffer from moderate anemia are a decrease from 58% to 42%, whereas adolescent girls who did not suffer from anemia experienced an increase to 35.4%. The result of this research concluded that iron supplementation among adolescent girl is the effectiveness of giving oral iron supplementation through “Gerakan Jumat Pintar” to hemoglobin that is increase 1.01 gr/dl.